Detecção de diazepam em larvas de moscas calliphoridae através de HPLC MS/MS - Marinheiro, Blenda Catarina de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Forensic entomology uses insects capable of colonizing decaying bodies and cadavers to help in criminal investigations as to raise evidence and solve cases. One of its areas is called entomotoxicology, which aims to identify chemical substances and analyze the possible effects of their presence in the development of insects. Thus, the current work aimed to identify the presence of diazepam in larvae of carrion flies from the Calliphoridae family through liquid chromatographymass spectrometry in tandem (HPLC MS/MS) as well as analyze the possible effects of this substance in their larval development. Diazepam was detected in all larvae (quantification values ranging from 9.9 to 1705 ng) but no alteration in average weight was observed when treatments DZP1 and DZP2 (1 μg/g and 2 μg/g, respectively) were compared to the control. Plus, no significative difference was observed between the treatments and the control regarding larval development and mortality. Thus, diazepam does not cause any morphological effects to the larvaes of Calliphoridae flies.
Monografia
Keywords: Entomologia forense; Entomotoxicologia; Calliphoridae; HPLC MS MS; Diazepam; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA